BIOMIMICRY: STUDYING NATURAL SYSTEMS FOR ACHIEVING SUSTAINABILITY - et. al., Purva Karmarkar (International Journal of Modern Agriculture, 2021)
Systems in nature are known to be the most efficient systems and humans have been taking inspiration from nature since the beginning of time. The science of incorporating nature’s highly efficient systems into human innovations is called as biomimicry. These systems also help in optimizing resource utilization and enhancing nature conservation. This study tries to understand the concept of biomimicry and find out whether biomimicry can be used a tool for achieving sustainable development. Furthermore, the study also emphasizes on the advent of biomimicry as a concept in modern technology and the trends in implementing the same in recent innovations.